2017
DOI: 10.1101/198390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolving building blocks of rhythm: How human cognition creates music via cultural transmission

Abstract: Short Title (<50 characters): How cognition creates rhythm via cultural evolutionAbstract (<200 words): Musical rhythm, in all its cross-cultural diversity, exhibits several commonalities across world cultures. Traditionally, music research has been split in two fields. Some scientists focused on musicality, namely the human biocognitive predispositions for music, with an emphasis on cross-cultural similarities. Other scholars investigated music, seen as cultural product, focusing on the large variation in wor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
1
14
0
1
Order By: Relevance
“…When humans reproduce an initially randomly-timed rhythmic sequence, and this process is repeated in a cascade fashion within one or across several individuals, the sequence is subconsciously reshaped to be composed of IOIs related by small integer ratios (Figure 1A ; c.f. Polak et al, 2016 ; Ravignani et al, 2016 , 2018 ; Jacoby and McDermott, 2017 ).…”
Section: Integer Ratios and Musical Rhythmmentioning
confidence: 99%
“…When humans reproduce an initially randomly-timed rhythmic sequence, and this process is repeated in a cascade fashion within one or across several individuals, the sequence is subconsciously reshaped to be composed of IOIs related by small integer ratios (Figure 1A ; c.f. Polak et al, 2016 ; Ravignani et al, 2016 , 2018 ; Jacoby and McDermott, 2017 ).…”
Section: Integer Ratios and Musical Rhythmmentioning
confidence: 99%
“…Moreover, there are already some experimental results suggesting that single participants simply do not follow the same trajectories as traditions with multiple individuals. For instance, Claidière et al [47] have found, in a transmission chain with baboons, a higher performance and transmission fidelity in traditions with multiple participants than in individuals presented with their own earlier outputs (but see [78]).…”
Section: (I) What Sorts Of Evolutionary Dynamics Characterize Cumulatmentioning
confidence: 99%
“…Studying the biology-culture interface can be used to reconcile old, unproductive nature-nurture debates by potentially showing how cognitive biases and cultural transmission interact to deliver the rhythmic structure of speech. Work along these lines has been done for linguistic morphology 165 , poetry 166 , and musical rhythm 90,[167][168][169] . An experimental design similar to these studies could be used to show how domain-general biases are amplified by cultural transmission resulting in rhythmic patterns of speech.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%